Synthesis of Some 2-Thioxo-imidazolidin-4-one Derivatives and its Antimicrobial Activity. Issue 4 (2010) - Nasser, A. Jamal Abdul; Idhayadhulla, A.; Kumar, R. Surendra; Selvin, J.
Abstract : Series of newly prepared 3-{[2, 6-bis(4-substituted phenyl)-1- methylpiperidin-4- ylidene] amino}- 2-thioxo-imidazolidin-4-one derivatives (3a-3f ) have been synthesized by the cyclization of compound (2a-2f ), ethyl chloro acetate and fused sodium acetate. The chemical structures were confirmed by IR, 1 H NMR and elemental analysis. The synthesized compounds were screened for their antimicrobial activity against four antibacterial and four antifungal organisms.